2006
DOI: 10.1055/s-2006-951745
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Folic Acid Uptake by Catechins and Tea Extracts in Caco-2 Cells

Abstract: In this present study it was aimed to determine whether the catechins contained in green tea and the whole extracts of Camellia sinensis (Theaceae) inhibit the uptake of folic acid by Caco-2 cell monolayers. Our results indicate that (-)-epigallocatechin 3-gallate (EGCG) and (-)-epicatechin 3-gallate (ECG) inhibit cellular folic acid uptake with IC50 values of 34.8 micromol/L and 30.8 micromol/L, respectively. Furthermore, green and black tea extracts were also found to inhibit folic acid uptake with IC50 valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 26 publications
3
32
0
1
Order By: Relevance
“…Other phenolic compounds such as myricetin, quercetin and kaempferol can also be found in teas (14) and may also contribute to inhibition of 3 H-FA and 3 H-MTX uptake. In agreement with the results from Lemos et al (78) , green and black tea extracts, as well as two catechins contained in green tea (EGCG and epicatechin gallate (ECG)), were also found to inhibit FA uptake by Caco-2 cells (80) . The difference in the effect of red wine in relation to 3 H-FA uptake in Caco-2 cells (inhibition) (78) and rat jejunum (no effect) (60) can be explained by, at least, two important differences.…”
Section: Effect Upon [supporting
confidence: 91%
“…Other phenolic compounds such as myricetin, quercetin and kaempferol can also be found in teas (14) and may also contribute to inhibition of 3 H-FA and 3 H-MTX uptake. In agreement with the results from Lemos et al (78) , green and black tea extracts, as well as two catechins contained in green tea (EGCG and epicatechin gallate (ECG)), were also found to inhibit FA uptake by Caco-2 cells (80) . The difference in the effect of red wine in relation to 3 H-FA uptake in Caco-2 cells (inhibition) (78) and rat jejunum (no effect) (60) can be explained by, at least, two important differences.…”
Section: Effect Upon [supporting
confidence: 91%
“…Using an in vitro enzyme activity assay, we observed a time-and dose-dependent inhibition of dihydrofolate reductase activity by EGCG and a green tea extract (47). A recent cell culture study showed that certain gallated derivatives of green tea polyphenols, namely EGCG, the predominant catechin in green tea, and epicatechin gallate, inhibited folic acid uptake in Caco-2 cells (48). In our studies in rats, green tea extract significantly decreased serum 5-methyl-tetrahydrofolate concentrations (47).…”
Section: Current Status Of Knowledgesupporting
confidence: 52%
“…Such possible, yet unpredictable effects through (increased) tea consumption might arise from the enzymeand transporter-related interactions of such tea specimens [14,35,36]. Since several of their catechin-derived components (mainly EGCG and ECG) as well as black tea and green tea inhibited the uptake of folic acid in Caco-2 cells, suggesting a potential interaction during the absorption step [28], the present in vivo study was designed to challenge the hypothesis that tea extracts taken concomitantly with folic acid might diminish folate absorption and thus the systemic availability of folates also under clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Since nutritional intake of folic acid often might be at the lower level of dietary recommendations [26,27], possible food-and herb-interactions that may lead to a decreased systemic availability of folates could be critical. In this context, an in vitro interaction between folic acid and extracts of green and black tea as well as tea catechins at the level of cellular uptake using Caco-2 cell monolayers was demonstrated recently [28]. In that study, (-)-epigallocatechin-3-gallate (EGCG) and (-)-epicatechin-3-gallate (ECG) inhibited the cellular folic acid uptake with IC 50 values of 34.8 and 30.8 mmol/l, respectively.…”
Section: Introductionmentioning
confidence: 95%